2011
DOI: 10.1039/c1ee01726h
|View full text |Cite
|
Sign up to set email alerts
|

De-NOx in alternative lean/rich atmospheres on La1−xSrxCoO3 perovskites

Abstract: Herein, we introduce a La 1Àx Sr x CoO 3 perovskite catalyst, substituting for Pt containing LNT catalysts, to remove efficiently NO x from lean-burn engines. The NO x storage/reduction occurred alternatively on the perovskite in successive lean/rich atmospheres, and the NO x conversion reached 71.4% with 100% selectivity to N 2 at 300 C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 26 publications
3
72
0
1
Order By: Relevance
“…The E v values of the La-ter models were greater than those of the Mn-ter models for all Sr-doping models, suggesting that O-vacancies preferred to form on the Mn-ter surface, rather than the La-ter surface, i.e. 7,31,32 Overall, the effect of Sr is to promote the oxidation activity and O-vacancy formation in the LaMnO 3 (001) planes. The results are in agreement with the discussion of the electronic structures in Fig.…”
Section: O-vacancy Formation Energymentioning
confidence: 91%
See 1 more Smart Citation
“…The E v values of the La-ter models were greater than those of the Mn-ter models for all Sr-doping models, suggesting that O-vacancies preferred to form on the Mn-ter surface, rather than the La-ter surface, i.e. 7,31,32 Overall, the effect of Sr is to promote the oxidation activity and O-vacancy formation in the LaMnO 3 (001) planes. The results are in agreement with the discussion of the electronic structures in Fig.…”
Section: O-vacancy Formation Energymentioning
confidence: 91%
“…[1][2][3] In a common NSR catalyst, Pt/BaO/Al 2 O 3 , NO is oxidized to NO 2 on Pt and subsequently adsorbed on BaO as a nitrate species in the lean-burn period. 7,8 The oxidation activity depends on the reducibility, oxygen mobility within the lattice, and the surface defects. Recently, Sr-doped perovskite oxides (ABO 3 ) were discovered to be efficient platinum substitutes in diesel oxidation and NSR reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Li et al. [34] demonstrated that these lanthanum based perovskites exhibit a high NOx conversion and N 2 selectivity for different gas composition. Furthermore, it was proved that the incorporation of Fe into the perovskite structure improves the sulfur tolerance of the catalysts [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Looking for alternatives for current platinum-based NSR catalysts, mixed oxides with perovskite structure have been recently used for NOx storage and reduction [26][27][28][29][30][31][32][33][34][35][36]. Thus, Ueda et al [30] employed a (La 0.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li et al [9] proposed a perovskite-based, Pt free lean NO x trap (LNT) catalyst shows promising NO x storage capacities. However, it is limited by its regeneration during the rich phase.…”
Section: Introductionmentioning
confidence: 99%